Application of the Hiwar Method in Arabic Subjects at MTs Ulumul Quran Teladan - Haradha Tunnisa (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This study aims to determine the process of learning Arabic in class VIII students of MTs Ulumul Quran Teladan, to determine the application of the hiwar method in learning Arabic, to determine the supporting factors and inhibiting factors of the implementation of the hiwar method in class VIII of MTs Ulumul Quran Teladan. This research is a type of qualitative research using data collection techniques through observation, documentation, interviews and questionnaires. data analysis is carried out through the stages of data reduction, data presentation, and conclusions or verification. The validity of the data was tested by extending attendance, increasing persistence, and triangulation of sources, triangulation of techniques, and triangulation of time. The results of this study indicate that (1) The process of learning Arabic for class VIII students of MTs Ulumul Quran Teladan in principle consists of opening activities, core activities, and closing activities. (2) The application of the hiwar method in learning Arabic for class VIII students of MTs Ulumul Quran Teladan is done by choosing simple materials that are in accordance with the abilities of students. Educators have applied the hiwar method in accordance with the steps of the method, so that the learning objectives can be achieved. (3) The factors that support the application of the hiwar method to class VIII students of MTs Ulumul Quran Teladan are the interests of students, textbooks, educators and the factors that hinder the application of the hiwar method are mufradat, self-confidence, and the school environment.